Pulsed Laser Deposition Method Used to Grow SiC Nanostructure on Porous Silicon Substrate: Synthesis and Optical Investigation for UV-Vis Photodetector Fabrication - Reem Alzubaidi; Makram A. Fakhri; László Pohl (Thermo)
In this study, a thin film of silicon carbide (SiC) was deposited on a porous silicon (P-Si) substrate using pulsed laser deposition (PLD). The photo–electrochemical etching method with an Nd: YAG laser at 1064 nm wavelength and 900 mJ pulse energy and at a vacuum of 10−2 mbar P-Si was utilized to create a sufficiently high amount of surface area for SiC film deposition to achieve efficient SiC film growth on the P-Si substrate. X-ray diffraction (XRD) analysis was performed on the crystalline structure of SiC and showed high-intensity peaks at the (111) and (220) planes, indicating that the substrate–film interaction is substantial. Surface roughness particle topography was examined via atomic force microscopy (AFM), and a mean diameter equal to 72.83 nm was found. Field emission scanning electron microscopy (FESEM) was used to analyze surface morphology, and the pictures show spherical nanoparticles and a mud-sponge-like shape demonstrating significant nanoscale features. Photoluminescence and UV-Vis spectroscopy were utilized to investigate the optical properties, and two emission peaks were observed for the SiC and P-Si substrates, at 590 nm and 780 nm. The SiC/P-Si heterojunction photodetector exhibited rectification behavior in its dark I–V characteristics, indicating high junction quality. The spectral responsivity of the SiC/P-Si observed a peak responsivity of 0.0096 A/W at 365 nm with detectivity of 24.5 A/W Jones, and external quantum efficiency reached 340%. The response time indicates a rise time of 0.48 s and a fall time of 0.26 s. Repeatability was assured by the tight clustering of the data points, indicating the good reproducibility and stability of the SiC/P-Si deposition process. Linearity at low light levels verifies efficient photocarrier generation and separation, whereas a reverse saturation current at high intensities points to the maximum carrier generation capability of the device. Moreover, Raman spectroscopy and energy dispersive spectroscopy (EDS) analysis confirmed the structural quality and elemental composition of the SiC/P-Si film, further attesting to the uniformity and quality of the material produced. This hybrid material’s improved optoelectronic properties, achieved by combining the stability of SiC with the quantum confinement effects of P-Si, make it useful in advanced optoelectronic applications such as UV-Vis photodetectors.